Faktor Yang Mempengaruhi Terjadinya Retur Surat Perintah Pencairan Dana Di Kantor Pelayanan Perbendaharaan Negara (KPPN) Bandar Lampung - Cahyanti, Tri; Puspita, Indah Lia; Luthfi, Muhammad; Mudrikah, Ritali Evi (Universitas Malahayati, 2024)
This study aims to determine the factors that influence the return of orders for disbursement of funds at the Bandar Lampung State Treasury Service Office (KPPN) and efforts to resolve them. The type of research used in this research is observation and interviews. The approach used in this study is a qualitative approach. The results of this study show that the factors that influence the return of orders for disbursement of funds at the Bandar Lampung State Treasury Service Office (KPPN) are Human Resource Management Factors, Work Unit Factors (Satker), Time Management Factors, Bank Operational Factors, and efforts to resolve them, namely KPPN submit a SP2D return notification letter attached with a SP2D Return List no later than 7 working days, then the Satker submits an Account Rectification/Repair Letter to the KPPN attached with SPTJM, PPSPM signature and 10,000 stamp duty.